A four‐group urine risk classifier for predicting outcomes in patients with prostate cancer. (25th June 2019) - Connell, Shea P.; Yazbek‐Hanna, Marcelino; McCarthy, Frank; Hurst, Rachel; Webb, Martyn; Curley, Helen; Walker, Helen; Mills, Rob; Ball, Richard Y.; Sanda, Martin G.; Pellegrini, Kathryn L.; Patil, Dattatraya; et al.
Abstract : Objectives: To develop a risk classifier using urine‐derived extracellular vesicle (EV)‐RNA capable of providing diagnostic information on disease status prior to biopsy, and prognostic information for men on active surveillance (AS). Patients and Methods: Post‐digital rectal examination urine‐derived EV‐RNA expression profiles ( n = 535, multiple centres) were interrogated with a curated NanoString panel. A LASSO‐based continuation ratio model was built to generate four prostate urine risk (PUR) signatures for predicting the probability of normal tissue (PUR‐1), D'Amico low‐risk (PUR‐2), intermediate‐risk (PUR‐3), and high‐risk (PUR‐4) prostate cancer. This model was applied to a test cohort ( n = 177) for diagnostic evaluation, and to an AS sub‐cohort ( n = 87) for prognostic evaluation. Results: Each PUR signature was significantly associated with its corresponding clinical category ( P < 0.001). PUR‐4 status predicted the presence of clinically significant intermediate‐ or high‐risk disease (area under the curve = 0.77, 95% confidence interval [CI] 0.70–0.84). Application of PUR provided a net benefit over current clinical practice. In an AS sub‐cohort ( n = 87), groups defined by PUR status and proportion of PUR‐4 had a significant association with time to progression (interquartile range hazard ratio [HR] 2.86, 95% CI 1.83–4.47; P < 0.001). PUR‐4, when used continuously, dichotomized patient groups with differential progression rates of 10% and 60% 5 years after urine collection (HR 8.23, 95% CI 3.26–20.81; P < 0.001). Conclusion: Urine‐derived EV‐RNA can provide diagnostic information on aggressive prostate cancer prior to biopsy, and prognostic information for men on AS. PUR represents a new and versatile biomarker that could result in substantial alterations to current treatment of patients with prostate cancer.